Understanding Cultural Beliefs of a Good Death by Older People in South Korea: An Integrative Review of the Literature. Issue 6 (26th December 2022) - Yun, Kyoungsun; Jo, Minjeong; Lee, Yunji
Abstract : With the enforcement of the Hospice and Palliative Care and Decisions on Life-Sustaining Treatment for Patients at the End-of-Life Act in 2018, interest in the quality of death in South Korea is increasing. However, few studies have provided an updated perspective on a good death. This integrative review describes the attributes of a good death from the perspective of South Korean older adults. Among the 32 studies included in this review, 16 main themes representing good death were identified. Themes of maintaining dignity, not burdening others, living a meaningful life, being pain-free, and being prepared to die were commonly reported attributes of a good death in other cultures; themes further reflected in Korean culture were filial piety and parenting. In contrast, older adult characteristics such as low income and education level, bereavement experience, disease uncertainty, and depressive symptoms were associated with high levels of fear of death or negative attitudes, such as trying to avoid suffering through death. This review provides insights into the health care provider's approach to older people at the end of their life in South Korea. Consequently, this can help determine potential unmet needs that can be improved.